Electrochemical Studies of the Cycloaddition Activity of Bismuth(III) Acetylides Towards Organic Azides Under Copper(I)-Catalyzed Conditions - Nazarova, Antonina L.; Zayat, Billal; Fokin, Valery V.; Narayan, Sri R. (Frontiers in Chemistry, 2022)
Time-dependent monitoring of the reactive intermediates provides valuable information about the mechanism of a synthetic transformation. However, the process frequently involves intermediates with short lifetimes that significantly challenge the accessibility of the desired kinetic data. We report in situ cyclic voltammetry (CV) and nuclear magnetic resonance (NMR) spectroscopy studies of the cycloaddition reaction of organobismuth(III) compounds with organic azides under the copper(I)-catalyzed conditions. A series of bismuth(III) acetylides carrying diphenyl sulfone scaffolds have been synthesized to study the underlying electronic and steric effects of the tethered moieties capable of transannular oxygen O···Bi interactions and para-functionality of the parent phenylacetylene backbones. While belonging to the family of copper-catalyzed azide-alkyne cycloaddition reactions, the reaction yielding 5-bismuth(III) triazolide is the sole example of a complex catalytic transformation that features activity of bismuth(III) acetylides towards organic azides under copper(I)-catalyzed conditions. Stepwise continuous monitoring of the copper(I)/copper(0) redox activity of the copper(I) catalyst by cyclic voltammetry provided novel insights into the complex catalytic cycle of the bismuth(III)-triazolide formation. From CV-derived kinetic data, reaction rate parameters of the bismuth(III)acetylides coordination to the copper(I) catalyst (KA) and equilibrium concentration of copper species [cat]eq. are compared with the overall 5-bismuth(III)triazolide formation rate constant kobs obtained by 1H NMR kinetic analysis.